2004
DOI: 10.2151/jmsj.2004.639
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Properties of Mid-latitude Frontal Ice-Clouds Observed by the Shortwave and Longwave Radiometer-Sondes

Abstract: In the Japanese Cloud and Climate Study (JACCS) cirrus experiment, simultaneous measurements of cloud radiative and microphysical properties were conducted by using the combined-sonde (radiometersonde þ hydrometeor-video-sonde (HYVIS)) observation system at the Meteorological Research Institute (MRI), located at (36.05 N, 140.13 E) in Tsukuba, Japan, during early summer seasons from 1995 to 1999. We have analyzed the radiative properties of frontal ice-clouds observed by the shortwave and longwave radiometer-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…4i and j). Radiative heating occurred due to shortwave radiation inside the cloud, while radiative cooling occurred due to longwave radiation around the cloud top (Yoshida et al, 2004). Shortwave cloud radiative heating and longwave cloud radiative cooling were both strong at the higher altitudes over the Kuroshio (126-128 • E, Fig.…”
Section: Mean Atmospheric Conditions and Cloud Properties In The Ecsmentioning
confidence: 96%
“…4i and j). Radiative heating occurred due to shortwave radiation inside the cloud, while radiative cooling occurred due to longwave radiation around the cloud top (Yoshida et al, 2004). Shortwave cloud radiative heating and longwave cloud radiative cooling were both strong at the higher altitudes over the Kuroshio (126-128 • E, Fig.…”
Section: Mean Atmospheric Conditions and Cloud Properties In The Ecsmentioning
confidence: 96%
“…The solar radiation budget and the cloud radiative properties (reflectance, transmittance, and absorptance) have been computed for the assumed cloudatmosphere column between the altitudes of 3.5 km (C404 flight level) and 0.3 km (B200 flight level). A description of the radiative transfer scheme used in this study can be found in Yoshida et al (2004), but with some modifications described below. The temperature and humidity profiles measured through the aircraft experiment were employed up to 2.5 km, and above 2.5 km they were adjusted to the radiosonde profile measured at the JMA Yonago Observatory (35.26 N,133.21 E) on that morning at 09:00 (LST).…”
Section: Radiative Properties For Solar Radiationmentioning
confidence: 99%
“…On the other hand, the scattering properties of ice particles (including snow crystals) were calculated by anomalous diffraction theory (ADT) with a gamma size distribution (Mitchell et al 1996). By using the experimental area-/massdimensional relationships for various shapes of ice particles, the ADT can calculate the extinction and absorption coefficients of ice particles more exactly than Mie-theory can do for ice spheres with equivalent-area and/or volumes (e.g., Yoshida et al 2004). Here, we assumed ice crystals of polycrystal shape from the ice particle images taken by the 2D-C probe (twodimensional optical array spectrometer) onboard B200 (see Fig.…”
Section: Radiative Properties For Solar Radiationmentioning
confidence: 99%
“…This is because ice-clouds usually have larger optical thicknesses and radiative effects than aerosols do, even though ice-clouds generally appear in the upper troposphere where the measurement errors of the SL radiometer-sondes get worse. Actually, the SL radiometer-sondes were used to measure the radiative properties of mid-latitude frontal ice-clouds in the JACCS cirrus experiment (Yoshida et al 2004). …”
Section: Performance Tests Of the Sl Radiometer-sondementioning
confidence: 99%
“…These sondes were connected in series to a balloon. The combined-sonde observation scheme and the JACCS cirrus experimental results are discussed in a separate paper (Yoshida et al 2004).…”
Section: Introductionmentioning
confidence: 99%